2020
DOI: 10.1021/acs.jcim.0c00030
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights into Molecular Activation and Positive Cooperative Mechanisms of FFAR1 Modulators

Abstract: Free fatty acid receptor 1 (FFAR1), a member of class A in G-protein-coupled receptors (GPCRs), is a promising antidiabetic target. The crystal structure of FFAR1 revealed that one agonist (MK-8666) binds to the extracellular vestibule of this receptor, while another (AP8) occupies the surface pocket between transmembrane (TM) helices TM4 and TM5. In this study, we performed 1 μs unbiased molecular dynamics (MD) simulation on each of five systems, to uncover why two ligands in completely different sites both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…By examining the trajectories from the MD simulations, we found that both ( R )-AM-8596 and ( S )-AM-8596 form salt bridge interactions with R183 5.39 and R258 7.35 (Figure A–D). Such salt bridge interactions have also been observed in the crystal structures 4PHU and 5TZR. , The computational and experimental studies on FFAR1 have shown that residues R183 5.39 and R258 7.35 are critical for the activity of agonists bound at site 1. , Compared with ( R )-AM-8596, ( S )-AM-8596 forms stronger salt bridge interactions with R183 5.39 and R258 7.35 (Figure A,B) (Table S2), which is most likely the main reason why ( S )-AM-8596 has a higher binding affinity to the FFAR1 than ( R )-AM-8596. In this work, R183 5.39 and R258 7.35 act like anchors and play a critical role in the ligand binding to FFAR1.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…By examining the trajectories from the MD simulations, we found that both ( R )-AM-8596 and ( S )-AM-8596 form salt bridge interactions with R183 5.39 and R258 7.35 (Figure A–D). Such salt bridge interactions have also been observed in the crystal structures 4PHU and 5TZR. , The computational and experimental studies on FFAR1 have shown that residues R183 5.39 and R258 7.35 are critical for the activity of agonists bound at site 1. , Compared with ( R )-AM-8596, ( S )-AM-8596 forms stronger salt bridge interactions with R183 5.39 and R258 7.35 (Figure A,B) (Table S2), which is most likely the main reason why ( S )-AM-8596 has a higher binding affinity to the FFAR1 than ( R )-AM-8596. In this work, R183 5.39 and R258 7.35 act like anchors and play a critical role in the ligand binding to FFAR1.…”
Section: Resultsmentioning
confidence: 56%
“…Such salt bridge interactions have also been observed in the crystal structures 4PHU 11 and 5TZR. 35 , 36 The computational and experimental studies on FFAR1 have shown that residues R183 5.39 and R258 7.35 are critical for the activity of agonists bound at site 1. 37 , 38 Compared with ( R )-AM-8596, ( S )-AM-8596 forms stronger salt bridge interactions with R183 5.39 and R258 7.35 ( Figure 3 A,B) ( Table S2 ), which is most likely the main reason why ( S )-AM-8596 has a higher binding affinity to the FFAR1 than ( R )-AM-8596.…”
Section: Resultsmentioning
confidence: 99%
“…Water is known to play an important role in protein-ligand interaction, protein function and molecular recognition [[ 66 ]]. The role of water in mediating the interaction of drug and protein was also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…T2DM is characterized by reduced secretion of insulin from β-cells and resulting hyperglycemia associated with cardiovascular complications such as cardiac ischemia and stroke [3,4]. Current methods to control blood sugar, including controlled diet, metformin, sulfonylurea, and insulin [5], have limited efficacy and are associated with potential health problems such as hypoglycemia, weight gain, and lack of sustained efficacy [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity was used as the logarithm of the half-maximal effective concentration (pEC 50 ), and the best model was statistically well-validated in terms of leave-one-out cross validation. Furthermore, the X-ray crystallographic structure of the binding mode in the FFA1 was elucidated [24], and molecular dynamics simulation [8] and experimental studies [25] clarify the activation mechanism of FFA1 to treat diabetes. Strong hydrogen bond interactions with Tyr-91, Arg-183, Asn-244, and Arg-258 are linked with higher agonist potency on the activation of FFA1 [26].…”
Section: Introductionmentioning
confidence: 99%